Predictors of Sports Organization at the Grass Root Sports Programmes Among Primary School Pupils in Kwara State - Dauda Olajide Rofiat Olusola (Indonesian Journal of Sport Management, 2022)
Sports organization at the grass-root sports competitions among primary school pupils plays a significant role in giving recognition to sports through identification and scouting of raw materials in Nigeria. School sports programmes at the primary schools level are, however, bedevilled with infrastructural, personnel, scheduling and funding challenges which render its organization a great setback. This study investigated the predictors of sports organization at the grass-root sports programmes among primary school pupils in Kwara state. The objectives of the study were to;(i) determine if knowledgeable and certified personnel has an influence on the sports organization at the grass root sports programmes among primary school pupils; (ii) determine if availability of sports infrastructures has influence on sports organization at the grass root sports programmes among primary school pupils; and (iii) determine if availability of sports resources has influence on sports organization at the grass root sports programmes among primary school pupils in Kwara State. Descriptive research design of survey method with total population of 197 (100%) from 50 primary schools pupils in Kwara state was adopted. Stratified, simple random and proportionate sampling techniques were employed to select 108 males and 72 females which comprised of principals, vice principals, physical education teachers and sport officers which were (91%) proportionately done with the help of research advisor. A researcher-developed questionnaire was used to gather data, validated experts in the field. A correlation co-efficient ‘r’ of 0.78 was obtained through test re-test method. Data collection was conducted with assistance of two trained research assistants. Frequency and percentages were used to analyze the demographic information of respondents and research questions while the five formulated null hypotheses were tested using the inferential statistics of chi-square at 0.05 level of significance. The findings from the study were that; i knowledgeable and certified personnel has a significant influence on sports organization at the grass root sports programmes among primary school pupils in Kwara state with the calc. X2 value of 231.104 ˃ table value of 21.03 at 12 degree of freedom @ 0.05 alpha level; ii availability of sports infrastructures has a significant on influence sports organization at the grass root sports programmes among primary school pupils in Kwara state with the calc. X2 value of 170.003 ˃ table value of 16.92 at 9 degree of freedom @ 0.05 alpha level; iii availability of sports resources has a significant influence on sports organization at the grass root sports programmes among primary school pupils in Kwara state with the calc. X2 value of 113.012 ˃ table value of 16.92 at 9 degree of freedom @ 0.05 alpha level. Based on the findings, the study concluded that knowledgeable and certified personnel, availability of sports infrastructures, availability of sports resources significantly influenced the sports organization at the grass root sports programmes among primary school pupils in Kwara state. The study recommended that having enough and qualified physical education teachers, quality infrastructures and sufficient sports resources, will greatly improve and enhance grass root sports programmes among primary schools pupils in Kwarastate.